Airfield safety and capacity improvements : case studies on successful projects - Baskir, Geoffrey S.; Gervais, Edward L. (American Society of Civil Engineers, 2013)
This book presents six case studies focused on the planning, engineering, and management of major construction projects at active airports. The construction or reconstruction of runways, aprons, ramps, or terminals while an airport is open for regular operations poses complex challenges, such as access to and from airport operating areas, logistics, staging, short-term lighting and signage, airline-airport communications, and staging and planning for short-term closures of taxiways and taxi lanes. Each case study describes the requirements, objectives, challenges, methodologies, and lessons learned from a recent project, offering unique insights into how complex projects can be managed successfully. These case studies are essential reading for those involved in planning, designing, and constructing capital improvements to airport facilities, including transportation and aviation engineers, construction engineers and project managers, and managers with airport authorities. --